Is the handgrip strength influential factor on the competition result in elite male artistic gymnasts? - Miloš Paunović; Dušan Đorđević; Dragan Marinković; Saša Veličković; Petar Veličković; Nedim Čović; Damira Vranešić-Hadžimehmedović; Amel Mekić; Eldin Jelešković; Mario Kozul; Lucija Milčić; Robert Bobinec; et al. (Journal of Men's Health, 2023)
High handgrip strength in men’s artistic gymnastics is crucial, mainly for improving performance and to potentially prevent injuries, as well as for the fact that gymnasts body movements are around immovable apparatuses (pommel horse, rings, parallel bars and high bar) for the extended period of time. Since there are not so many studies that have dealt with this topic and on actual competition, we have aimed to examine the handgrip strength influence on the competition result in elite male artistic gymnasts. The sample of participants were conducted of 37 elite male artistic gymnasts (8–21 years old), from 8 different countries as national team competitors at the International Competition “Laza Krstić and Marica Dželatović” held in Novi Sad, Serbia. Basic anthropometric measurements were included (body height, body weight and Body Mass Index (BMI)), along with training experience and handgrip strength measurement (both dominant and nondominant hand). Kolmogorov-Smirnov Z test (p < 0.05) was used for distribution normality, along with regression analysis with Model 1 (participants age, training experience, body height, body weight and BMI), Model 2 (Model 1 + dominant handgrip strength) and Model 3 (Model 1 + nondominant handgrip strength). SPSS v.20 was used for all statistical analysis. Our study have revealed that there is significant influence of all 3 Models on the parallel bars final result (p = 0.033; p = 0.049; p = 0.031, respectively), in terms of all set of variables, whereas body weight Beta scores (28.6%; 30.3%; 32.7%, respectively) moslty explains the results. Both dominant and nondominant handgrip strength are influential factors only on the parallel bars final result. Since both hands are contributing equally, bilateral training is necessary. In order to expand the knowledge on this topic and completely understand the influential factors, future studies are needed on this sample. Regardless of our main findings, our results should be taken with caution.